Assessment-of-utilization-of-Contraceptives-among-Women-in-Effutu-Municipality-in-the-Central-Region, Ghana - Christiana Asiedu1 (University of Cape Coast, 2019)
The aim of the Ghana National Contraceptive Security is to provide a conceptual approach at achieving a Contraceptive Prevalence Rate (CPR) of 50 percent by 2020. Despite the various activities carried out by Reproductive Health Unit (RHU) across the country on contraceptives, there is an unmet need of 35 percent which largely could be as a result of wrong perceptions or certain myths people have on contraceptives and side effects associated with them. The study accessed the utilization of contraceptives among women (15 – 49 years) in Effutu Municipality in the Central Region. Descriptive cross-sectional survey design was used to collect quantitative data. Questionnaire was used to collect the data from 277 women. A multi-stage sampling technique was used to select the respondents. Statistical Package for Solutions and Service (SPSS) version 21.0 and Microsoft Office Excel (2013) were be used to analyze the data collected. The results demonstrate that the knowledge and utilization level on contraceptives was high (87%). The results show that contraceptive use is greatly influence by husband’s approval. Educational programmes on family planning should target men so as that they could allow their partners to use contraceptives. It is recommended that there should be an intensification of educational programmes particularly to address the issue of side-effects perceived to be associated with the use of contraceptives.
Keywords: Contraceptives; Prevalence Rate; Reproductive Health; Utilization